The response of organic matter in Pennsylvanian coals in the North China Basin to rapid heating by magmatic intrusion - Bangjun Liu; Jiazhong Huang; James C. Hower; Achim Bechtel; Vivian A. Edwards; Wenmu Guo; Zeqi Tian; Shiming Liu; Lin Xiao; Cunliang Zhao (Organic Geochemistry, 2026)

3-OH-FA- and branched GDGT-based temperature calibrations from a transect of lakes in the eastern USA - Changhai Hou; Michael L. Griffiths; Alice Hardman; Osamu Seki; Aifeng Zhou; Sarah Greene; Elizabeth W. Patterson; Roland Indriksons; Sabrina Ryan; Michael DaSilva; Matthew Allison; Lin Chen; et al. (Organic Geochemistry, 2026)

Compartmentalized hydrogel-based in situ fibrous bed bioreactor (isFBB) for spatially controlled multi-strain anaerobic human gut microbial growth - Zubeen J. Hathi; James M.W.R. McElhinney; Ramachandran Chelliah; Manideep Pabba; Blaise L. Tardy; Anshu Priya; Carol Sze Ki Lin; Srinivas Mettu (Chemical Engineering Journal, 2026)

Vanadium salt inhibits osteoclast formation and preserves bone integrity in a rat model of type-1 diabetes associated bone loss - Joshua Greendyk; James Thornton; Darian Napoleon; Michael Greenberg; Anthony Lin; Mike Levidy; Jonathan R. Lopez; Maximilian Muñoz; Kevin Innella; Yazan Kadkoy; Maya Deza Culbertson; Jessica A. Cottrell; et al. (BioMetals, 2026)

Accelerating wastewater-based SARS-CoV-2 surveillance using a mobile laboratory in mixed infrastructure regions - Amirmohammad Sakhaei; Soroosh Torabi; Mohammad Dehghan Banadaki; Alexus Rockward; William D. Strike; Soroush Farahbakhsh; David Graf; August Bodin; Amanda Muzzey; Riley Lang; Sara Ignoffo; Sean Haley; et al. (Science of The Total Environment, 2026)

Standardized microhaplotype databases and frameworks for assessing and mining crop genetic diversity - Dongyan Zhao; Meng Lin; Cristiane H. Taniguti; Alexander M. Sandercock; Shufen Chen; Ebrahiem Babiker; Nahla V. Bassil; E. Charles Brummer; Jose Roberto Camacho; Warren Chatwin; Shu-Yun Chen; Shaun J. Clare; et al. (Theoretical and Applied Genetics, 2026)
Keymessage Standardized microhaplotype databases for eight diverse crops enable multiallelic analyses, comparative genetics, and breeding decisions. Abstract Microhaplotypes are short genomic segments that contain multiple tightly linked variants, providing multi-allelic data that can enhance genetic resolution compared to traditional biallelic single nucleotide polymorphism (SNP) markers. Here, we present the creation and utilization of separate microhaplotype databases for eight crop species representing diverse genome sizes, ploidy levels, and breeding systems. We developed a standardized, species-agnostic pipeline for processing, filtering, and databasing microhaplotypes generated using the DArTag targeted genotyping platform. To enhance user accessibility, we developed a no-code, user-friendly application, HapApp, that uses an R Shiny front-end interface to allow breeders and researchers to add unique, standardized microhaplotype identities from raw DArTag reports and iteratively update the existing crop-specific database with the newly discovered microhaplotypes. Selected case studies with these databases highlight the operational advantages of microhaplotypes, especially for challenging, highly heterozygous, or polyploid species. They offer an informative alternative to traditional biallelic SNP analyses for resolving population structures and improving linkage map ordering. This integrated framework provides a reproducible and scalable foundation for managing and exploiting microhaplotype data in plant breeding and genetic research, enabling robust cross-project comparisons and facilitating trait discovery in both simple and complex crop genomes, while enabling comparative genomics and cross-species functional transfer that accelerates genetic gains across all crop species.

Processes affecting pollution fluxes during the coastal erosion of legacy colliery wastes - Ian T. Burke; Sebastian J. Pitman; James Hodson; Lin Niu; Fatmah Mohammed; Jenni Ilari Skakunova; Alex L. Riley; Catherine J. Gandy; Elliot Whitehead; Karen A. Hudson-Edwards; Elin Jennings; Helen Jay; et al. (Applied Geochemistry, 2026)

The Response of Soil Enzyme Activities to Functionally-Diverse Cover Crop Mixtures in Citrus Orchards Depends on Cover Crop Duration in Sandy Soils - Kendall Mackin; Sarah L. Strauss; Yang Lin; Yaslin Gonzalez; James Colee; Gabriel Maltais-Landry (Journal of Soil Science and Plant Nutrition, 2026)

Hierarchical learning creates invariant schema within plastic neural networks - James R. Elder; Jie Zheng; Lydia B. Shimelis; Ueli Rutishauser; Milo M. Lin (Journal of Computational Neuroscience, 2026)

Waste fire surveillance: A case study using remote sensing data and IoT ground sensing for monitoring fires at waste management sites - Theodros Woldeyohannes; Yan Lin; Xiaoyang Zhang; John Doyle; Margaret Eggers; Zhuoming Liu; Al Ekram Hridoy; El Mehdi Bimaghra; Tadiwanashe Bizure; Blair Mirka; Latasha James; Joseph Hoover (Waste Management, 2026)

A two-step Bayesian clustering approach to relate PFAS mixture profiles and dietary patterns in early pregnancy - Xuzhi Wang; Tamarra James-Todd; Ami R. Zota; Luke Shawler; Pi-I.D. Lin; Emily Oken; Jorge Chavarro; Sharon Sagiv; Briana J.K. Stephenson (Environmental Research, 2026)

Novel Hybrid Machine Learning Algorithms for Porosity Prediction Using Well Log Data from Triassic Reservoirs of the Tahe Oilfield in China - Mohammed Albashir; Lin Pan; Xiao Wang; Wahib Yahya; Abdelmottaleb Aldoud; Hatim Quer; Mohamed Elfatih Salaim; Faulo James (Natural Resources Research, 2026)

Possible inter-room aerosol-mediated COVID-19 transmission in a quarantine hotel: A case study - Merrill LIM; Junjing YANG; Sze Tat TAN; Man XIAO; Chun Ping GAO; Vernon LEE; Yee Leong TEOH; James CHAN; Lin CUI; Yichen DING; Joanna SHEN; Ruixin LI; et al. (Building and Environment, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Susceptibility to eight common chemical insecticides in Helicoverpa zea populations from the southern United States - Bhavana Patla; Tiago Silva; Shucong Lin; Graham P. Head; Francis P.F. Reay-Jones; Xinzhi Ni; Lina Bernaola; Sebe Brown; Don Cook; James Villegas; Jeffrey A. Davis; Fangneng Huang (Crop Protection, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Drought, Conflict and the Use of Historical Data and Methodologies in Interdisciplinary Palaeoclimatic Research - Helen Foxhall Forbes; Mateusz Fafinski; Guy Halsall; James M. Harland; Dan Lawrence; Kelly Clarke-Neish; Lin Foxhall; Michele Abballe; Massimiliano Borroni; Ismini Lypiridou; Vicky Manolopoulou; Anastasia Nikulina; et al. (Climatic Change, 2026)
A major challenge in the interdisciplinary study of past climates is ensuring that evidence and data relating to different disciplines are analysed effectively using appropriate methodologies. In ‘Droughts and conflict during the late Roman period’, Clim. Chang 178, 2025, Norman et al. argue that historical sources support their conclusions that drought contributed causally to the ‘barbarian conspiracy’ of 367CE and to other late Roman conflicts. Although historians have developed rigorous methodologies for effective analysis and interpretation of surviving texts, the authors outline no methodologies for dealing with the textual evidence. Further, there are issues with the historical ‘conflict’ and numismatic datasets and with their interpretation. We focus on four major evidential points: 1) the ‘barbarian conspiracy’, 2) the agricultural economy; 3) the ‘conflict’ dataset and 4) the coin dataset. Historical evidence relating to drought and famine in the late Roman Empire does exist: future interdisciplinary research may indeed offer interesting observations on the relationships between drought and conflict, but the textual evidence discussed by Norman et al. does not, and cannot, support the authors’ assertions. Effective interdisciplinary research must allow all disciplines to engage on their own terms and with their own accepted standards of rigour.

Identifying trend reversals in atmospheric ethane from a multi-site analysis - Marina Friedrich; Siem Jan Koopman; Yicong Lin; Emmanuel Mahieu; Stephan Smeekes; Martine De Mazière; Victoria Flood; Matthias Max Frey; Michel Grutter; James W. Hannigan; Frank Hase; Nicholas Jones; et al. (Climatic Change, 2026)
Ethane is the most abundant non-methane hydrocarbon in Earth’s atmosphere and acts as an indirect greenhouse gas, influencing the atmospheric lifetime of methane. Therefore, understanding the development of trends and identifying trend reversals in atmospheric ethane is crucial. Ethane abundance is measured at different ground-based stations worldwide using Fourier transform infrared remote sensing techniques. We compile a new dataset comprising 26 ethane time series from the Northern and Southern Hemispheres. We analyze their long-term trends using different econometric techniques capable of handling missing data and strong seasonal components present in the data. The resulting trend patterns are consistent across the different methods, with similar estimated trends at the various stations. In the Northern Hemisphere, the common trend across stations declined from the 1990s to 2005, gradually increased over the next decade, and then resumed a similar downward trajectory from 2015 onward. The estimated trends reveal a pronounced peak around 2014/2015, marking a reversal from an upward to a downward trend.

Multi-contaminants in road runoff of a compact city: Characteristics, interactions, and ecological risks - Yinghong Lin; Brigitte Helmreich; Yuen-Wa Ho; James Kar-Hei Fang; Chunling Luo; Yuhong Wang (Water Research, 2026)

Interpretable data-driven modeling of total phosphorus dynamics from 2005 to 2024 in a large shallow lake - Weipeng Lin; Yongqiang Zhou; Ze Ren; Wei Zou; Hongwei Guo; Na Li; Yunlin Zhang; James Elser; R. Iestyn Woolway; Kun Shi; Guangwei Zhu; Boqiang Qin; et al. (Water Research, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Advancements in environmental microplastic removal and upcycling techniques - Tianyu Lin; Penggang Li; Huaping Jia; Heng Jiang; Fengjia Xie; Yanting Liu; James Kar-Hei Fang; Changchao Li; Xuming Zhang (Journal of Environmental Chemical Engineering, 2026)

Ocean Heat Content Sets Another Record in 2025 - Yuying Pan; Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Juan Du; Zhankun Wang; Andrea Storto; Karina Von Schuckmann; Yujing Zhu; Michael E. Mann; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2026)
Global ocean warming continued unabated in 2025 in response to increased greenhouse gas concentrations and recent reductions in sulfate aerosols, reflecting the long-term accumulation of heat within the climate system, with conditions evolving toward La Niña during the year. In 2025, global upper 2000 m ocean heat content (OHC) increased by ∼23 ± 8 ZJ relative to 2024 according to IAP/CAS estimates. CIGAR-RT, and Copernicus Marine data confirm the continued ocean heat gain. Regionally, about 33% of the global ocean area ranked among its historical (1958–2025) top three warmest conditions, while about 57% fell within the top five, including the tropical and South Atlantic Ocean, Mediterranean Sea, North Indian Ocean, and Southern Oceans, underscoring the broad ocean warming across basins. Multiple datasets consistently indicate ocean warming, as measured by 0–2000 m OHC, increased from 0.14 ± 0.03 W m −2 (10 yr) −1 during 1960–2025 to 0.32 ± 0.14 W m −2 (10 yr) −1 during 2005–2025 (IAP/CAS), the latter being consistent with EEI (Earth’s Energy Imbalance) estimates within uncertainties. In contrast, the global annual mean sea surface temperature (SST) in 2025 was 0.49°C above the 1981–2010 baseline and 0.12 ± 0.03°C lower than in 2024 (IAP/CAS; similar in CMA-SST, FY3 MWRI SST, ERSSTv5 and Copernicus Marine data), consistent with the development of La Niña conditions, but still ranking as the third-warmest year on record.

Spermidine carbon quantum dots as an alternative antimicrobial agent for hatcheries rearing Pacific white shrimp (Litopenaeus vannamei) - Hung-Yun Lin; Han-Tso Lin; Yun-Ru Chiang; Ya-Yun Lu; James Pan; Hou-Ju Lin; Wan-Ching Kuo; Han-Jia Lin; Han-You Lin (Aquaculture, 2026)

Genome-enabled elucidation of nitrogen removal pathways in Thauera sp. strain SND5 - Qingkun Wang; Yifan Zhang; Chen Chen; Matthew James Rogers; Kun-Lin Yang; Jianzhong He (Water Research, 2026)

Rapid and selective gold recovery from waste random access memory in a non-aqueous solvent acetic anhydride - Duy Tho Tran; Ngoc Tu Trinh Tran; Greeshma James; Xiaoyu Lin; Myung-Hee Song; Yeoung-Sang Yun (Resources, Conservation and Recycling, 2026)

Revisiting the Anti-Drug Antibody Assay Drug Tolerance of a Commercial Biological Product - James Zanghi; Nancy Yu; Benjamin T. Andrews; Phyllis Chan; Maxime Usdin; Cecilia Chiu; WeiYu Lin; Alyse Lin; Yuan Song (The AAPS Journal, 2025)
Drug tolerance (DT) is a critical attribute of anti-drug antibody (ADA) assays for assessing clinical immunogenicity. We present a unique situation where a previously approved commercial product, atezolizumab, required re-assessment of the assay DT to meet an increased drug exposure demand arising from a new route of administration (subcutaneous) and align with updated health authority (HA) regulations. Rather than redevelop the existing ADA assay, which could disrupt ongoing clinical trials, we identified a new anti-idiotype (anti-ID) antibody surrogate that demonstrated that the assay maintained adequate DT for the new route of administration. This streamlined approach addressed concerns regarding higher serum trough concentrations with subcutaneous administration and stricter sensitivity expectations. We established a target DT concentration based on population pharmacokinetic modeling to ensure adequate ADA characterization at steady state. This case study highlights the value of having alternative surrogate ADAs and demonstrates that achieving stringent DT requirements can be accomplished without extensive method redevelopment. We also introduce the broader implications of surrogate ADA selection, binding kinetics, and the clinical relevance of achieving high DT in the context of atezolizumab's efficacy and safety profile. This work also emphasizes the importance of considering bioanalytical assay characteristics, such as DT, throughout a product’s lifecycle. Graphical Abstract

Seawater-conditioned cement as a viable substrate for coral larval settlement - Elizaldy Acebu Maboloc; Jason Hon-Yin Szeto; Ken Chue-Ho Yuen; Shirley Chun-Ching Wong; Juan Carlos Astudillo; Lin Cai; Lucen Hao; Shipeng Zhang; Apple Pui-Yi Chui; James Kar-Hei Fang (Regional Studies in Marine Science, 2025)

How effective are green roofs as building carbon sinks? Empirical evidence linking substrate, depth, and vegetation dynamics in the U.S. Great Plains - M.M. Lekhon Alam; Lee R. Skabelund; Charles W. Rice; James S. Lin; Jaeyoung Ha (Journal of Environmental Management, 2025)

Indian summer monsoon variability across the last 9000 years: New evidence from stalagmites of southwestern China - Yanzhen Li; Chunju Huang; Jianghu Lan; David B. Kemp; James G. Ogg; Ashish Sinha; Lvfan Chen; Xiqian Wang; Huiru Tang; Xu Lin; Khalaf H.M. Abdel-Raheem; Rui Zhang; et al. (Global and Planetary Change, 2025)

Modified Intracranial Aneurysm Rupture Rat Model with Angiographic Imaging - William Wei-Lin Pan; Masahiko Itani; Kostadin Karagiozov; Teppei Komatsu; Hiroki Ohta; Hirokazu Koseki; Shunsuke Hataoka; Yoshiki Arakawa; Hirotaka James Okano; Tomohiro Aoki; Yuichi Murayama (Translational Stroke Research, 2025)

Bacterial community formation on plastic and glass in coral reefs - Yusuke Iwaki; Kohei Hamamoto; Fabian Gösser; Chengze Li; Jeffrey Jolly; Sen-Lin Tang; Timothy Ravasi; James Davis Reimer (Coral Reefs, 2025)

Fracture influence on karst development in carbonate reservoirs: Insights from the Lichuan karst region, Hubei, China - Hadi Hussain; Lu Yun; Fei Cao; Min Yang; Yan Wang; Xinhua Li; Lin Pan; Xiao Wang; Wakeel Hussain; Faulo James (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Influence of Pearl river plume and coastal upwelling on planktonic foraminiferal assemblages in the northern South China Sea - Rick J. Yang; Hui-Ling Lin; Tai-Chun Lin; Jay Lee; James T. Liu; Horng-Sheng Mii (Marine Environmental Research, 2025)

Linking source-to-sink processes, organic matter composition, and oxygen consumption on a shallow passive margin shelf sustained by small mountainous rivers - Yu-Shih Lin; Chih-Lin Wei; Yuan-Pin Chang; Jih-Terng Wang; Shu-Ying Chuang; Liang-Chi Wang; James T. Liu; Hong-Chun Li; Chieh-Wei Hsu (Geochimica et Cosmochimica Acta, 2025)

Consumption of fermented Cd and Pb contaminated wheat flour increases potential health risk - Weiqin Xing; Zhexu Si; James A. Ippolito; Guobing Lin; Farzana Kastury; Sen Ma; Kunyan Qiu; Linlin Zhao; Lena Q. Ma; Liping Li (Food and Chemical Toxicology, 2025)

A bifunctional fluorescent probe for simultaneous imaging of myelin integrity and β-amyloid plaques in Alzheimer's disease progression - Xueting Wang; Huan Liu; Xueao Wang; He Wang; Jie Lin; Xiangjie Luo; Jian-Jun Yang; Bing Zhang; Guiquan Chen; Hai-Liang Zhu; Tony D. James; Yong Qian (Chemical Engineering Journal, 2025)

Real-Time agricultural image encryption algorithm using AES on edge computing devices - Mohammad Ashik Alahe; Young Chang; James Kemeshi; Kwanghee Won; Xufei Yang; Lin Wei (Computers and Electronics in Agriculture, 2025)

Optimizing biogas residue composting: Impact of biochar and zeolite co-loaded with lignocellulose-degrading microbial agents on degradation, humification, and microbial ecology - Hong Chang; Ruian Lin; Xiaohong Su; Xinrui Xu; Wei Liu; Yilin Zhang; Zeyan Mu; Xin Wang; Anina James; Junting Pan (Journal of Environmental Chemical Engineering, 2025)

In-situ geotechnical properties of abyssal sediments and implications for environmental impacts of polymetallic nodule mining - Zhenggang Li; Zhou Li; James R. Hein; Yangrui Cheng; Yuwei Liu; Shiquan Lin; Hao Wang; Xibin Han; Yanhui Dong; Fengyou Chu; Xiaohu Li (Marine Geology, 2025)

Characterizing ancient seep environments by in-situ sulfur isotope composition of authigenic pyrite - Qinyi Zhang; Zhiyong Lin; Harald Strauss; Tingting Chen; Yang Lu; James L. Goedert; Jörn Peckmann (Chemical Geology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Monitoring pelagic Sargassum in the Atlantic Ocean from space: Principles and practices - Chuanmin Hu; Brian B. Barnes; Lin Qi; James F.R. Gower; Junnan Jiao; Yuyuan Xie (Harmful Algae, 2025)

Reversal of practical resistance in fall armyworm to Cry1F maize: a case report on the resistance to susceptibility in Bt crops from the southeastern USA - Tiago Silva; Gregory A. Sword; Andie Miller; Jawwad A. Qureshi; Graham P. Head; Dawson D. Kerns; Juan Luis Jurat-Fuentes; James Villegas; Tyler B. Towles; Xinzhi Ni; Francis P. F. Reay-Jones; Daniel Carrillo; et al. (Journal of Pest Science, 2025)

QTL mapping and whole-genome sequencing analysis for novel genetic resources associated with sucrose content in soybean [Glycine max (L.) Merr.] - Dongho Lee; Tri D. Vuong; James G. Shannon; Qijian Song; Feng Lin; Henry T. Nguyen (Theoretical and Applied Genetics, 2025)
Key message A major QTL for sucrose content was mapped on chromosome 8 in PI 506593. The novel genetic variants and candidate genes were further identified within the major QTL. Abstract Sucrose in soybean [ Glycine max (L.) Merr.] contribute to animal feed efficiency and natural sweetness of soy products. Thus, identifying novel genetic resources, such as quantitative trait loci (QTL), associated with sucrose content in soybean is essential for enhancing seed values. In this study, two recombinant inbred line populations derived from the same high sucrose donor parent, PI 506593, were used to identify significant QTLs. A total of 11 sucrose-related regions on chromosomes (Chrs.) 4, 5, 6, 8, 10, and 13 were identified using QTL analysis. Among them, four QTLs ( qSUC_08.1 , qSUC_08.2 , qSUC_08.3 , and qSUC_08.4 ) were clustered in the interval of 40,597,410–42,861,364 bp on Chr. 8, which was considered major QTL region. A desirable marker at 41,834,095 bp was tested in two populations, showing that two phenotypically extreme groups were efficiently differentiated. We further identified 44 and 54 candidate genes with non-synonymous mutations in the major QTL region based on the annotations of Wm82.a2.v1 and Wm82.a5.v1 assemblies, respectively. Among 54 candidate genes from Wm82.a5.v1, Protein Variation Effect Analyzer (PROVEAN) revealed that 18 genes contained 34 variants that had deleterious impacts on biological functions. RNA-seq analysis highlighted five candidate genes that were highly expressed in pod and seed tissues during reproductive stages and other plant parts. A gene, Gm_Wm82_23219 ( Glyma.08G293800 , Wm82.a2.v1) encoding proline-rich protein 4-like, was highlighted in both PROVEAN and RNA-seq analyses. Novel findings in this study will be valuable genetic resources in soybean breeding programs that aim to improve efficiency in animal feed and human food.

Blockade of A2AR improved brain perfusion and cognitive function in a mouse model of Alzheimer’s disease - Mariana Sayuri Berto Udo; Julia Zaccarelli-Magalhães; Garrett Alan Clemons; Cristiane Teresinha Citadin; Julia Langman; Drew James Smith; Luiz Henrique Matuguma; Vesna Tesic; Hung Wen Lin (GeroScience, 2025)

Assessing greenspace and cardiovascular health through deep-learning analysis of street-view imagery in a cohort of US children - Li Yi; Sheryl Rifas-Shiman; Marcia Pescador Jimenez; Pi-I Debby Lin; Esra Suel; Perry Hystad; Andrew Larkin; Steve Hankey; Wenwen Zhang; Jochem Klompmaker; Emily Oken; Marie-France Hivert; et al. (Environmental Research, 2025)

Characterization and ecological risks of microplastics in urban road runoff - Yinghong Lin; Yuhong Wang; Yuen-Wa Ho; James Kar-Hei Fang; Yuan Li (Science of The Total Environment, 2024)

Site selection and effects of background towers on urban CO2 estimates: A case study from central downtown Zhengzhou in China - Ge Ren; Kailun Du; Anna Karion; Shiqi Zhao; Israel Lopez-Coto; Xiaoning Wang; James Whetstone; Hong Lin (Environmental Research, 2024)

Cyber security in smart agriculture: Threat types, current status, and future trends - Mohammad Ashik Alahe; Lin Wei; Young Chang; Sainath Reddy Gummi; James Kemeshi; Xufei Yang; Kwanghee Won; Mazhar Sher (Computers and Electronics in Agriculture, 2024)

Manipulate dynamic chemical interactions in renewable polymers for 3D printing tunable, healable, and recyclable metamaterials - Yuchao Wu; Cheng Qiu; Karla J. Silva; Jaeho Shin; Shaoyun Wang; Bujingda Zheng; Zhenru Chen; Guoliang Huang; James M. Tour; Jian Lin (Chemical Engineering Journal, 2024)

A streamlined method to generate endothelial cells from human pluripotent stem cells via transient doxycycline-inducible ETV2 activation - Allen Chilun Luo; Jiuhai Wang; Kai Wang; Yonglin Zhu; Liyan Gong; Umji Lee; Xiang Li; Daniel M. Tremmel; Ruei-Zeng Lin; Donald E. Ingber; James Gorman; Juan M. Melero-Martin (Angiogenesis, 2024)

Finding Hopf bifurcation islands and identifying thresholds for success or failure in oncolytic viral therapy - Sana Jahedi; Lin Wang; James A. Yorke; James Watmough (Mathematical Biosciences, 2024)

Zirconium isotope tracing of the magmatic-hydrothermal transition - Er-Lin Zhu; Qiong-Xia Xia; Shao-Bing Zhang; James Van Orman; Ren-Xu Chen; Zhao-Ya Li; Peng Gao (Geochimica et Cosmochimica Acta, 2024)

The role of perceived negative partner behavior in daily snacking behavior: A dynamical systems approach - Jingrun Lin; Jennifer K. MacCormack; Steven M. Boker; James A. Coan; Sarah C.E. Stanton (Appetite, 2024)

Size-dependent deleterious effects of nano- and microplastics on sperm motility - Ziyi Lin; Zijie Li; Shuqin Ji; Hoi Shing Lo; Baki Billah; Ayesha Sharmin; Xiaofang Han; Wing-yee Lui; William Ka Fai Tse; James Kar-Hei Fang; Chunqiu Zhang; Xuejun Shang; et al. (Toxicology, 2024)

Evidence for large-scale, long-term highly siderophile element heterogeneities in the Atlantic mantle from Leg 153 and 209 peridotites - Yin-Zheng Lin; James M.D. Day; Diana B. Brown; Jason Harvey; Chuan-Zhou Liu (Geochimica et Cosmochimica Acta, 2024)

Number of global change factors alters plant-soil feedbacks via its effect on soil fungal communities - Wei Xue; Lin Huang; James D. Bever; Cheng Du; Hao-Ming Yuan; Lin-Xuan He; Xiao-Mei Zhang; Fei-Hai Yu (Soil Biology and Biochemistry, 2024)

Microplastics from face mask impairs sperm motility - Ziyi Lin; Zijie Li; Shuqin Ji; Hoi Shing Lo; Baki Billah; Ayesha Sharmin; Wing-yee Lui; William Ka Fai Tse; James Kar-Hei Fang; Keng Po Lai; Lei Li (Marine Pollution Bulletin, 2024)

Climate-regulation of organic carbon export in erosive mountain settings: A case study from Taiwan since the last glacial maximum - Li-Wei Zheng; Robert G. Hilton; Yuan-Pin Chang; Rick J. Yang; Xiaodong Ding; Xufeng Zheng; Tsung-Yu Lee; Hsi-Jih Lu; Jung-Tai Lu; Yu-Shih Lin; James T. Liu; Shuh-Ji Kao (Quaternary Science Reviews, 2024)

Determination of fatty acid uptake and desaturase activity in mammalian cells by NMR-based stable isotope tracing - Penghui Lin; James Sledziona; Kubra B. Akkaya-Colak; Maria M. Mihaylova; Andrew N. Lane (Analytica Chimica Acta, 2024)

Morphology and chemical composition of Taiwan oil millet (Eccoilopus formosanus) epicuticular wax - Marita Anggarani; Yu-Ying Lin; Shao-An Fang; Hshin-Ping Wu; Chi-Chih Wu; Wann-Neng Jane; Thomas James Roscoe; Frederic Domergue; Yue-Ie Caroline Hsing (Planta, 2024)

Evaluating the Educational Value of Cancer Registries — a Systematic Review and Thematic Analysis - James Lin; Hugo C. Temperley; Kirsten Larkins; Caitlin Waters; Kit Loong Chong; Jack Maida; David Proud; Adele Burgess; Alexander Heriot; Philip Smart; Helen Mohan (Journal of Cancer Education, 2024)

Inherited BRCA1 and RNF43 pathogenic variants in a familial colorectal cancer type X family - James M. Chan; Mark Clendenning; Sharelle Joseland; Peter Georgeson; Khalid Mahmood; Jihoon E. Joo; Romy Walker; Julia Como; Susan Preston; Shuyi Marci Chai; Yen Lin Chu; Aaron L. Meyers; et al. (Familial Cancer, 2024)
Genetic susceptibility to familial colorectal cancer (CRC), including for individuals classified as Familial Colorectal Cancer Type X (FCCTX), remains poorly understood. We describe a multi-generation CRC-affected family segregating pathogenic variants in both BRCA1 , a gene associated with breast and ovarian cancer and RNF43 , a gene associated with Serrated Polyposis Syndrome (SPS). A single family out of 105 families meeting the criteria for FCCTX (Amsterdam I family history criteria with mismatch repair (MMR)-proficient CRCs) recruited to the Australasian Colorectal Cancer Family Registry (ACCFR; 1998–2008) that underwent whole exome sequencing (WES), was selected for further testing. CRC and polyp tissue from four carriers were molecularly characterized including a single CRC that underwent WES to determine tumor mutational signatures and loss of heterozygosity (LOH) events. Ten carriers of a germline pathogenic variant BRCA1 :c.2681_2682delAA p.Lys894ThrfsTer8 and eight carriers of a germline pathogenic variant RNF43 :c.988 C > T p.Arg330Ter were identified in this family. Seven members carried both variants, four of which developed CRC. A single carrier of the RNF43 variant met the 2019 World Health Organization (WHO 2019 ) criteria for SPS, developing a BRAF p.V600 wildtype CRC. Loss of the wildtype allele for both BRCA1 and RNF43 variants was observed in three CRC tumors while a LOH event across chromosome 17q encompassing both genes was observed in a CRC. Tumor mutational signature analysis identified the homologous recombination deficiency (HRD)-associated COSMIC signatures SBS3 and ID6 in a CRC for a carrier of both variants. Our findings show digenic inheritance of pathogenic variants in BRCA1 and RNF43 segregating with CRC in a FCCTX family. LOH and evidence of BRCA1-associated HRD supports the importance of both these tumor suppressor genes in CRC tumorigenesis.

Comparing thermoregulatory responses between short and long moderate intensity intermittent exercise protocols with the same duty cycle - Tze-Huan Lei; Chien Lin; Tatsuro Amano; Anna Ooue; Toby Mündel; James David Cotter; Naoto Fujii; Takeshi Nishiyasu; Narihiko Kondo (Journal of Thermal Biology, 2024)

Climate-dependent effectiveness of nonpharmaceutical interventions on COVID-19 mitigation - Juping Ji; Hao Wang; Lin Wang; Pouria Ramazi; Jude Dzevela Kong; James Watmough (Mathematical Biosciences, 2023)

Use of reconstituted kefir consortia to determine the impact of microbial composition on kefir metabolite profiles - Benjamin C.T. Bourrie; Natalie Diether; Ryan P. Dias; Seo Lin Nam; A. Paulina de la Mata; Andrew J. Forgie; Gautam Gaur; James J. Harynuk; Michael Gänzle; Paul D. Cotter; Benjamin P. Willing (Food Research International, 2023)

Large-diameter trees buffer monsoonal changes to tree biomass over two decades - Chen-Chia Ku; Jianwu Tang; Wei-Chun Chao; Kuo-Jung Chao; Guo-Zhang Michael Song; Huan-Yu Lin; James A. Lutz (Plant Ecology, 2023)

Enzymatically hydrolyzed fluorescence-based chemical probe enables in situ mapping of chitinase activity in the rhizosphere - Elias K. Zegeye; Vivian S. Lin; Jamie R. Nuñez; Nick A. Sconzo; Samuel O. Purvine; Aaron T. Wright; James J. Moran (Soil Biology and Biochemistry, 2023)

Mapping smallholder cashew plantations to inform sustainable tree crop expansion in Benin - Leikun Yin; Rahul Ghosh; Chenxi Lin; David Hale; Christoph Weigl; James Obarowski; Junxiong Zhou; Jessica Till; Xiaowei Jia; Nanshan You; Troy Mao; Vipin Kumar; et al. (Remote Sensing of Environment, 2023)

Stable chromium isotope compositions of hydrogenetic ferromanganese crusts potentially linked to primary productivity - Xiangli Wang; Jian-Ming Zhu; Guangliang Wu; Wenjing Liu; Cheng Lin; Wei Yang; Zhifang Xu; James R. Hein (Chemical Geology, 2023)

Reconstructing population exposures to acrylamide from human monitoring data using a pharmacokinetic framework - Yu-Sheng Lin; Viktor Morozov; Abdel-Razak Kadry; James L Caffrey; Wei-Chun Chou (Chemosphere, 2023)

A photocured bio-based shape memory thermoplastics for reversible wet adhesion - Yuchao Wu; Changhua Su; Shaoyun Wang; Bujingda Zheng; Alireza Mahjoubnia; Kianoosh Sattari; Hanwen Zhang; James Meister; Guoliang Huang; Jian Lin (Chemical Engineering Journal, 2023)

Dietary exposure to nTiO2 reduces byssus performance of mussels under ocean warming - Saishuai Li; Hui Chen; Chunhua Liu; Inna M. Sokolova; Yuchuan Chen; Fujing Deng; Zhe Xie; Li'ang Li; Wei Liu; James Kar-Hei Fang; Daohui Lin; Menghong Hu; et al. (Science of The Total Environment, 2023)

Obliquity forcing of continental aquifers during the late Paleozoic ice age - Ren Wei; Mingsong Li; Rui Zhang; Yongyun Hu; James G. Ogg; Guoyong Liu; He Huang; Xiangwu He; Shuai Yuan; Qifan Lin; Zhijun Jin (Earth and Planetary Science Letters, 2023)

BasinMaker 3.0: A GIS toolbox for distributed watershed delineation of complex lake-river routing networks - Ming Han; Hongren Shen; Bryan A. Tolson; James R. Craig; Juliane Mai; Simon G.M. Lin; Nandita B. Basu; Frezer S. Awol (Environmental Modelling & Software, 2023)

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

The contrast in suspended particle dynamics at surface and near bottom on the river-dominated northern South China Sea shelf in summer: implication on physics and biogeochemistry coupling - Jay Lee; James T. Liu; Yu-Shih Lin; Chen-Tung Arthur Chen; Bo-Shian Wang (Frontiers in Marine Science, 2023)
To understand the process-response relations among physical forcing and biogeochemical properties of suspended particles (SPs) in the river-dominated northern South China Sea shelf, a 5-day shipboard observation was conducted at a fixed location on the dispersal pathway of the Zhujiang (Pearl) River plume (ZRP) in the summer of 2016. Instrumented moorings were deployed near the sampling site to record the flow and wave fields every 10 minutes. Hydrographic properties were measured hourly to identify different water masses. Water and SPs samples at the surface (3 m) and near the bottom (3 m above the bed) were taken every 3 h for the analyses of nutrients, chlorophyll-a (Chl-a), and particulate organic matter (POM including POC, PN, and δ 13 C POC ). Meanwhile, the grain-size composition of SPs and seafloor sediment were also analyzed. Results showed that monsoon winds drove cold upwelling and ZRP waters at the surface. Both the upwelling and ZRP regimes contained newly produced marine phytoplankton based on low POC/Chl-a ratio (PC ratio) and enriched δ 13 C POC. However, SPs in the ZRP regime were smaller (<153 µm), having denser particle bulk density, and less enriched δ 13 C POC , indicating different bio-communities from the upwelling regime. EOF analysis of the surface data suggested that mixing processes and the dispersal of the ZRP regime were mainly controlled by far-field storm winds, tidal modulation, and strength of mixing. On the other hand, a bottom nepheloid layer (BNL) was observed, mainly consisting of SPs<63 μm with higher bulk density than SPs at the surface. POM in the BNL was degraded and δ 13 C POC -depleted according to the PC ratio and δ 13 C POC . EOF analysis of the near-bottom data indicated that the dominant physical processes influencing the biogeochemical properties of SPs in the BNL were jointly the upwelling-associated lateral transport (first order) and tide-related resuspension (second order). Our study identified the contrast between the surface and near-bottom regimes with the coupling patterns among physical forcing and physiochemical properties of SPs using good constraints on particle dynamics and particle sources.

Intestinal response of mussels to nano-TiO2 and pentachlorophenol in the presence of predator - Xiang Chen; Wei Huang; Chunhua Liu; Hanting Song; Khor Waiho; Daohui Lin; James K.H. Fang; Menghong Hu; Kit Yue Kwan; Youji Wang (Science of The Total Environment, 2023)

Incongruities in recently revised radiofrequency exposure guidelines and standards - James C. Lin (Environmental Research, 2023)

Centenarian clocks: epigenetic clocks for validating claims of exceptional longevity - Eric Dec; James Clement; Kaiyang Cheng; George M. Church; Michael B. Fossel; David H. Rehkopf; Luis Rosero-Bixby; Michael S. Kobor; David TS. Lin; Ake T. Lu; Zhe Fei; Wei Guo; et al. (GeroScience, 2023)
Claims surrounding exceptional longevity are sometimes disputed or dismissed for lack of credible evidence. Here, we present three DNA methylation-based age estimators (epigenetic clocks) for verifying age claims of centenarians. The three centenarian clocks were developed based on n = 7039 blood and saliva samples from individuals older than 40, including n = 184 samples from centenarians, 122 samples from semi-supercentenarians (aged 105 +), and 25 samples from supercentenarians (aged 110 +). The oldest individual was 115 years old. Our most accurate centenarian clock resulted from applying a neural network model to a training set composed of individuals older than 40. An epigenome-wide association study of age in different age groups revealed that age effects in young individuals (age < 40) are correlated ( r = 0.55) with age effects in old individuals (age > 90). We present a chromatin state analysis of age effects in centenarians. The centenarian clocks are expected to be useful for validating claims surrounding exceptional old age.

Soil organic carbon, aggregation and fungi community after 44 years of no-till and cropping systems in the Central Great Plains, USA - James S. Lin; Marcos V. M. Sarto; Tiffany L. Carter; Dallas E. Peterson; Colleen Gura; Laura Mino; Megan Rohrs; Hallie Lucas; Jamie Clark; Charles W. Rice (Archives of Microbiology, 2023)

On the occurrence of low concentration hyperpycnal river plumes in a small mountainous river-canyon system - Sheng-De Tsai; Yu-Chi Lin; Andhy Romdani; Jia-Lin Chen; Ray T. Hsu; James T. Liu (Continental Shelf Research, 2023)

Infusing satellite data into aerosol forecast for near real-time episode detection and diagnosis in East Asia - Sheng-Po Chen; Cheng-Hsuan (Sarah) Lu; James E. Davies; Chang-Feng Ou-Yang; Neng-Huei Lin; Amy K. Huff; Bradley R. Pierce; Shobha Kondragunta; Jia-Lin Wang (Science of The Total Environment, 2023)

An assessment tool for estimating effects of entrainment at hydropower facilities on adfluvial fish populations - Hsien-Yung Lin; Eduardo G. Martins; Michael Power; James A. Crossman; Alf J. Leake; Steven J. Cooke (Environment Systems and Decisions, 2022)

Groundwater vulnerability assessment of shallow aquifer in the South Texas sand sheet using a GIS-based DRASTIC model - Syed Istiyak Ahmed; Chu-Lin Cheng; Juan Gonzalez; James J. Kang; Jungseok Ho; Leslie Soto-Sanchez (Modeling Earth Systems and Environment, 2022)

Copper ore material footprints and transfers embodied in domestic and international trade of provinces in China - Lin Liu; Heinz Schandl; James West; Meng Jiang; Zijian Ren; Dingjiang Chen; Bing Zhu (Journal of Industrial Ecology, 2022)
Copper is a critical material for development and plays a profound role in transitioning to a low‐carbon future. China is the main copper consumer in recent decades that has a fast‐growing domestic market accompanied by active international trade. Given the large regional differences within China, it is relevant to understand the domestic driving forces of copper demands and the cascading effects on international regions. Here we combine the newly developed copper ore extraction datasets and the Chinese interprovincial nested global multi‐regional input–output models to explore the copper ore material footprints (CuMF), the interprovincial CuMF transfers, and the international CuMF transfers of provinces. Results show that at the initial stage of clean energy development (2007–2012), most provinces in China are, to a great degree (∼50%), relatively reliant on international copper inputs. The manufacturing sector is the main driving force of international CuMF transfers while the construction sector drives most interprovincial CuMF transfers, with the total volume of international CuMF transfers recently tripling. The central provinces in the industrial transition period and the northwestern provinces in the initial development stage saw the fastest growth in international and interprovincial CuMF transfers, respectively. The economic growth and low‐carbon transition will further advance copper‐related manufacturing and construction activities while other evidences indicate that the degree of foreign inputs to meet copper demand may peak and the interprovincial supply may rise continuously. Targeted governance of these sectors may effectively reduce high dependence on the international copper supply and ensure an efficient interprovincial CuMF transfer pattern.

Tisch Cancer Institute Scholars Program: Mentored Cancer Research Training Pipeline for Medical Students - Kaitlyn Ben-David; Jenny J. Lin; James L. M. Ferrara; Janice L. Gabrilove (Journal of Cancer Education, 2022)

Chromosome-level Genome Assembly of Acanthopagrus latus Provides Insights into Salinity Stress Adaptation of Sparidae - Jianguo Lu; Dong Gao; Ying Sims; Wenyu Fang; Joanna Collins; James Torrance; Genmei Lin; Jingui Xie; Jian Liu; Kerstin Howe (Marine Biotechnology, 2022)

Anomaly and cyber fraud detection in pipelines and supply chains for liquid fuels - Alinne Beteto; Vidal Melo; Jessica Lin; Marwan Alsultan; Eduardo Mario Dias; Elizabeth Korte; DeAndre A. Johnson; Negin Moghadasi; Thomas L. Polmateer; James H. Lambert (Environment Systems and Decisions, 2022)

Prevalence, complete genome, and metabolic potentials of a phylogenetically novel cyanobacterial symbiont in the coral‐killing sponge, Terpios hoshinota - Yu‐Hsiang Chen; Hsing‐Ju Chen; Cheng‐Yu Yang; Jia‐Ho Shiu; Daphne Z. Hoh; Pei‐Wen Chiang; Wenhua Savanna Chow; Chaolun Allen Chen; Tin‐Han Shih; Szu‐Hsien Lin; Chi‐Ming Yang; James Davis Reimer; et al. (Environmental Microbiology, 2022)
Summary Terpios hoshinota is an aggressive, space‐competing sponge that kills various stony corals. Outbreaks of this species have led to intense damage to coral reefs in many locations. Here, the first large‐scale 16S rRNA gene survey across three oceans revealed that bacteria related to the taxa Prochloron , Endozoicomonas , SAR116, Ruegeria , and unclassified Proteobacteria were prevalent in T . hoshinota . A Prochloron ‐related bacterium was the most dominant and prevalent cyanobacterium in T . hoshinota . The complete genome of this uncultivated cyanobacterium and pigment analysis demonstrated that it has phycobiliproteins and lacks chlorophyll b , which is inconsistent with the definition of Prochloron . Furthermore, the cyanobacterium was phylogenetically distinct from Prochloron , strongly suggesting that it should be a sister taxon to Prochloron . Therefore, we proposed this symbiotic cyanobacterium as a novel species under the new genus Candidatus Paraprochloron terpiosi. Comparative genomic analyses revealed that ‘Paraprochloron’ and Prochloron exhibit distinct genomic features and DNA replication machinery. We also characterized the metabolic potentials of ‘Paraprochloron terpiosi’ in carbon and nitrogen cycling and propose a model for interactions between it and T. hoshinota . This study builds a foundation for the study of the T . hoshinota microbiome and paves the way for better understanding of ecosystems involving this coral‐killing sponge.

miR-146a-5p modulates cellular senescence and apoptosis in visceral adipose tissue of long-lived Ames dwarf mice and in cultured pre-adipocytes - Allancer D. C. Nunes; Moritz Weigl; Augusto Schneider; Sarah Noureddine; Lin Yu; Collin Lahde; Tatiana Dandolini Saccon; Kunal Mitra; Esther Beltran; Johannes Grillari; James L. Kirkland; Tamara Tchkonia; et al. (GeroScience, 2022)

Overall and central obesity and prostate cancer risk in African men - Ilir Agalliu; Wei-Kaung Jerry Lin; Janice S. Zhang; Judith S. Jacobson; Thomas E. Rohan; Ben Adusei; Nana Yaa F. Snyper; Caroline Andrews; Elkhansa Sidahmed; James E. Mensah; Richard Biritwum; Andrew A. Adjei; et al. (Cancer Causes & Control, 2022)

Individual Microcystis colonies harbour distinct bacterial communities that differ by Microcystis oligotype and with time - Derek J. Smith; James Y. Tan; McKenzie A. Powers; Xiaoxia N. Lin; Timothy W. Davis; Gregory J. Dick (Environmental Microbiology, 2021)

Hidden in plain sight: a molecular field survey of three wheat leaf blotch fungal diseases in North-Western Europe shows co-infection is widespread - Annemarie Fejer Justesen; Beatrice Corsi; Andrea Ficke; Lorenz Hartl; Sarah Holdgate; Lise Nistrup Jørgensen; Morten Lillemo; Min Lin; Ian J. Mackay; Volker Mohler; Melanie Stadlmeier; Kar-Chun Tan; et al. (European Journal of Plant Pathology, 2021)
Wheat ( Triticum aestivum L.) yields are commonly affected by foliar infection by fungal pathogens. Of these, three wheat leaf blotch fungal diseases, septoria nodorum blotch (SNB), tan spot (TS) and septoria tritici blotch (STB), caused by Parastagonospora nodorum ( Pn ), Pyrenophora tritici-repentis ( Ptr ) and Zymoseptoria tritici ( Zt ), respectively, induce major yield losses. Infection results in necrotic areas on the leaf, and it is often difficult to determine the underlying causative pathogen from visible symptoms alone, especially in mixed infections. Here, a regional survey of 330 wheat samples collected across three seasons (years 2015–2017) from four north-west European countries was undertaken. Using quantitative polymerase chain reaction (qPCR) assays specific for each pathogen, as well as disease assessment of leaf materials, distinct regional differences were identified. Two-thirds (65%) of all samples harbored at least two of the three pathogens. Norway had high SNB abundance, but also showed mixed infections of SNB, TS and STB. In Germany, TS was prevalent, with STB also common. Danish samples commonly possessed all three pathogens, with STB prevalent, followed by TS and SNB. The UK had a major prevalence of STB with minimal occurrence of TS and SNB. Across all samples, qPCR identified Zt , Pn and Ptr in 90%, 54% and 57% of samples, respectively. For each pathogen, average disease levels via visual assessment showed modest positive correlation with fungal DNA concentrations (R 2 = 0.13–0.32). Overall, our study highlights that the occurrence of mixed infection is common and widespread, with important implications for wheat disease management and breeding strategies.

Dietary inflammatory index and risk of colorectal adenoma: effect measure modification by race, nonsteroidal anti-inflammatory drugs, cigarette smoking and body mass index? - Fangcheng Yuan; Lin Deng; Xiangqing Sun; Zhengyi Chen; Nitin Shivappa; Ashutosh K. Sheth; Gregory S. Cooper; James R. Hebert; Li Li (Cancer Causes & Control, 2021)

Effect of water regime and harvest stage on essential oil accumulation in basil plant growing in sandy soil - João V. R. S. Souza; Lin Chau Ming; Marcos A. L. Santos; James E. Simon; Hector R. Juliani; João C. C. Saad (Irrigation Science, 2021)

Individual Microcystis colonies harbour distinct bacterial communities that differ by Microcystis oligotype and with time - Derek J. Smith; James Y. Tan; McKenzie A. Powers; Xiaoxia N. Lin; Timothy W. Davis; Gregory J. Dick (Environmental Microbiology, 2021)
Summary Interactions between bacteria and phytoplankton in the phycosphere have impacts at the scale of whole ecosystems, including the development of harmful algal blooms. The cyanobacterium Microcystis causes toxic blooms that threaten freshwater ecosystems and human health globally. Microcystis grows in colonies that harbour dense assemblages of other bacteria, yet the taxonomic composition of these phycosphere communities and the nature of their interactions with Microcystis are not well characterized. To identify the taxa and compositional variance within Microcystis phycosphere communities, we performed 16S rRNA V4 region amplicon sequencing on individual Microcystis colonies collected biweekly via high‐throughput droplet encapsulation during a western Lake Erie cyanobacterial bloom. The Microcystis phycosphere communities were distinct from microbial communities in whole water and bulk phytoplankton seston in western Lake Erie but lacked ‘core’ taxa found across all colonies. However, dissimilarity in phycosphere community composition correlated with sampling date and the Microcystis 16S rRNA oligotype. Several taxa in the phycosphere were specific to and conserved with Microcystis of a single oligotype or sampling date. Together, this suggests that physiological differences between Microcystis strains, temporal changes in strain phenotypes, and the composition of seeding communities may impact community composition of the Microcystis phycosphere.

Identification of eight QTL controlling multiple yield components in a German multi-parental wheat population, including Rht24, WAPO-A1, WAPO-B1 and genetic loci on chromosomes 5A and 6A - Beatrice Corsi; Lia Obinu; Camila M. Zanella; Saverio Cutrupi; Rob Day; Manuel Geyer; Morten Lillemo; Min Lin; Lorenzo Mazza; Lawrence Percival-Alwyn; Melanie Stadlmeier; Volker Mohler; et al. (Theoretical and Applied Genetics, 2021)
Key message Quantitative trait locus (QTL) mapping of 15 yield component traits in a German multi-founder population identified eight QTL each controlling ≥2 phenotypes, including the genetic loci Rht24 , WAPO-A1 and WAPO-B1 . Abstract Grain yield in wheat ( Triticum aestivum L.) is a polygenic trait representing the culmination of many developmental processes and their interactions with the environment. Toward maintaining genetic gains in yield potential, ‘reductionist approaches’ are commonly undertaken by which the genetic control of yield components, that collectively determine yield, are established. Here we use an eight-founder German multi-parental wheat population to investigate the genetic control and phenotypic trade-offs between 15 yield components. Increased grains per ear was significantly positively correlated with the number of fertile spikelets per ear and negatively correlated with the number of infertile spikelets. However, as increased grain number and fertile spikelet number per ear were significantly negatively correlated with thousand grain weight, sink strength limitations were evident. Genetic mapping identified 34 replicated quantitative trait loci (QTL) at two or more test environments, of which 24 resolved into eight loci each controlling two or more traits—termed here ‘multi-trait QTL’ (MT-QTL). These included MT-QTL associated with previously cloned genes controlling semi-dwarf plant stature, and with the genetic locus Reduced height 24 ( Rht24 ) that further modulates plant height. Additionally, MT-QTL controlling spikelet number traits were located to chromosome 7A encompassing the gene WHEAT ORTHOLOG OF APO1 ( WAPO-A1 ), and to its homoeologous location on chromosome 7B containing WAPO-B1 . The genetic loci identified in this study, particularly those that potentially control multiple yield components, provide future opportunities for the targeted investigation of their underlying genes, gene networks and phenotypic trade-offs, in order to underpin further genetic gains in yield.

Identification and cross-validation of genetic loci conferring resistance to Septoria nodorum blotch using a German multi-founder winter wheat population - Min Lin; Melanie Stadlmeier; Volker Mohler; Kar-Chun Tan; Andrea Ficke; James Cockram; Morten Lillemo (Theoretical and Applied Genetics, 2021)
Key message We identified allelic variation at two major loci, QSnb.nmbu-2A.1 and QSnb.nmbu-5A.1 , showing consistent and additive effects on SNB field resistance. Validation of QSnb.nmbu-2A.1 across genetic backgrounds further highlights its usefulness for marker-assisted selection. Abstract Septoria nodorum blotch (SNB) is a disease of wheat ( Triticum aestivum and T. durum ) caused by the necrotrophic fungal pathogen Parastagonospora nodorum . SNB resistance is a typical quantitative trait, controlled by multiple quantitative trait loci (QTL) of minor effect. To achieve increased plant resistance, selection for resistance alleles and/or selection against susceptibility alleles must be undertaken. Here, we performed genetic analysis of SNB resistance using an eight-founder German Multiparent Advanced Generation Inter-Cross (MAGIC) population, termed BMWpop. Field trials and greenhouse testing were conducted over three seasons in Norway, with genetic analysis identifying ten SNB resistance QTL. Of these, two QTL were identified over two seasons: QSnb.nmbu-2A.1 on chromosome 2A and QSnb.nmbu-5A.1 on chromosome 5A. The chromosome 2A BMWpop QTL co-located with a robust SNB resistance QTL recently identified in an independent eight-founder MAGIC population constructed using varieties released in the United Kingdom (UK). The validation of this SNB resistance QTL in two independent multi-founder mapping populations, regardless of the differences in genetic background and agricultural environment, highlights the value of this locus in SNB resistance breeding. The second robust QTL identified in the BMWpop, QSnb.nmbu-5A.1, was not identified in the UK MAGIC population. Combining resistance alleles at both loci resulted in additive effects on SNB resistance. Therefore, using marker assisted selection to combine resistance alleles is a promising strategy for improving SNB resistance in wheat breeding. Indeed, the multi-locus haplotypes determined in this study provide markers for efficient tracking of these beneficial alleles in future wheat genetics and breeding activities.

Fine-scale roadkill risk models: understanding the intersection of wildlife and roads - Kristina Chyn; Te-En Lin; David P. Wilkinson; James L. Tracy; A. Michelle Lawing; Lee A. Fitzgerald (Biodiversity and Conservation, 2021)

Brain structural connectomes indicate shared neural circuitry involved in subjective experience of cognitive and physical fatigue in older adults - Timothy M. Baran; Zhengwu Zhang; Andrew James Anderson; Kelsey McDermott; Feng Lin (Brain Imaging and Behavior, 2020)

Public Perceptions of Mangrove Forests Matter for Their Conservation - Farid Dahdouh-Guebas; Gordon N. Ajonina; A. Aldrie Amir; Dominic A. Andradi-Brown; Irfan Aziz; Thorsten Balke; Edward B. Barbier; Stefano Cannicci; Simon M. Cragg; Marília Cunha-Lignon; David J. Curnick; Carlos M. Duarte; et al. (Frontiers in Marine Science, 2020)

Testicular cancer in Hispanics: incidence of subtypes over time according to neighborhood sociodemographic factors in California - Mindy C. DeRouen; Meg McKinley; Sumit Anil Shah; Hala T. Borno; Rhonda Aoki; Daphne Y. Lichtensztajn; John T. Leppert; James D. Brooks; Benjamin I. Chung; Scarlett Lin Gomez; Iona Cheng (Cancer Causes & Control, 2020)

Coupling virio- and bacterioplankton populations with environmental variable changes in the Bohai Sea - Caixia Wang; Lin Wu; Yibo Wang; James S. Paterson; James G. Mitchell; Xiaoke Hu (Acta Oceanologica Sinica, 2020)

Genetic mapping using a wheat multi-founder population reveals a locus on chromosome 2A controlling resistance to both leaf and glume blotch caused by the necrotrophic fungal pathogen Parastagonospora nodorum - Min Lin; Beatrice Corsi; Andrea Ficke; Kar-Chun Tan; James Cockram; Morten Lillemo (Theoretical and Applied Genetics, 2020)
Key message A locus on wheat chromosome 2A was found to control field resistance to both leaf and glume blotch caused by the necrotrophic fungal pathogen Parastagonospora nodorum . Abstract The necrotrophic fungal pathogen Parastagonospora nodorum is the causal agent of Septoria nodorum leaf blotch and glume blotch, which are common wheat ( Triticum aestivum L.) diseases in humid and temperate areas. Susceptibility to Septoria nodorum leaf blotch can partly be explained by sensitivity to corresponding P. nodorum necrotrophic effectors (NEs). Susceptibility to glume blotch is also quantitative; however, the underlying genetics have not been studied in detail. Here, we genetically map resistance/susceptibility loci to leaf and glume blotch using an eight-founder wheat multiparent advanced generation intercross population. The population was assessed in six field trials across two sites and 4 years. Seedling infiltration and inoculation assays using three P. nodorum isolates were also carried out, in order to compare quantitative trait loci (QTL) identified under controlled conditions with those identified in the field. Three significant field resistance QTL were identified on chromosomes 2A and 6A, while four significant seedling resistance QTL were detected on chromosomes 2D, 5B and 7D. Among these, QSnb.niab - 2A.3 for field resistance to both leaf blotch and glume blotch was detected in Norway and the UK. Colocation with a QTL for seedling reactions against culture filtrate from a Norwegian P. nodorum isolate indicated the QTL could be caused by a novel NE sensitivity. The consistency of this QTL for leaf blotch at the seedling and adult plant stages and culture filtrate infiltration was confirmed by haplotype analysis. However, opposite effects for the leaf blotch and glume blotch reactions suggest that different genetic mechanisms may be involved.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Tropical cyclone sensitivities to CO2 doubling: roles of atmospheric resolution, synoptic variability and background climate changes - Gabriel A. Vecchi; Thomas L. Delworth; Hiroyuki Murakami; Seth D. Underwood; Andrew T. Wittenberg; Fanrong Zeng; Wei Zhang; Jane W. Baldwin; Kieran T. Bhatia; William Cooke; Jie He; Sarah B. Kapnick; et al. (Climate Dynamics, 2019)

A direct comparison of divalent metal-ion transporter (DMT1) and hinokitiol, a potential small molecule replacement - Michael D. Garrick; Laura M. Garrick; Lin Zhao; James F. Collins; Joleen Soukup; Andrew J. Ghio (BioMetals, 2019)

Tsunami Hazard and Built Environment Damage Observations from Palu City after the September 28 2018 Sulawesi Earthquake and Tsunami - Ryan Paulik; Aditya Gusman; James H. Williams; Gumbert Maylda Pratama; Sheng-lin Lin; Alamsyah Prawirabhakti; Ketut Sulendra; Muhammad Yasser Zachari; Zabin Ellyni Dwi Fortuna; Novita Barrang Pare Layuk; Ni Wayan Ika Suwarni (Pure and Applied Geophysics, 2019)

Environment‐ and trait‐mediated scaling of tree occupancy in forests worldwide - Haibao Ren; Petr Keil; Xiangcheng Mi; Keping Ma; Zhanqing Hao; Wanhui Ye; Luxiang Lin; Renato Valencia; Christine Dawn Fletcher; Duncan W. Thomas; Robert W. Howe; James Lutz; et al. (Global Ecology and Biogeography, 2019)
Aim The relationship between the proportion of sites occupied by a species and the area of a site [occupancy–area relationship (OAR)] offers key information for biodiversity management and has long fascinated ecologists. We quantified the variation in OAR for 3,157 woody species in 17 forest plots worldwide and tested the relative importance of environment and species traits for explaining this variation and evaluated overall model predictive ability. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We used mixed‐effect regression to examine the observed shape of the OAR (its “slope”) against species‐specific and plot‐wide predictors: coarse‐grain occupancy, tree size, plot species richness, energy availability and topographic complexity. Results We found large variation in OAR slopes, and the variation was strongest among species within plots. The OAR slopes showed a latitudinal trend and were steeper near the equator. As predicted, coarse‐grain occupancy and tree size negatively affected OAR slopes, whereas species richness had a positive effect and explained most of the variance between plots. Although hypothesized directionalities were broadly confirmed, traits and environment had relatively limited overall predictive power. Main conclusions These results document the variation of the OAR for 3,157 species at near‐global extent. We found a latitudinal gradient in OAR slopes and confirmed key hypothesized predictors. But at this global extent and over the large set of species analysed, the remaining unexplained variation in OAR slopes was substantial. Nevertheless, this large‐scale empirical analysis of the OAR offers an initial step towards a more general use of OARs for the fine‐scale prediction of species distributions and abundance.

Comparison of PM2.5 emission rates and source profiles for traditional Chinese cooking styles - Pengchuan Lin; Wanqing He; Lei Nie; James J. Schauer; Yuqin Wang; Shujian Yang; Yuanxun Zhang (Environmental Science and Pollution Research, 2019)

Biochar application as a tool to decrease soil nitrogen losses ( NH 3 volatilization, N 2 O emissions, and N leaching) from croplands: Options and mitigation strength in a global perspective - Qi Liu; Benjuan Liu; Yanhui Zhang; Tianlong Hu; Zhibin Lin; Gang Liu; Xiaojie Wang; Jing Ma; Hui Wang; Haiyang Jin; Per Ambus; James E. Amonette; et al. (Global Change Biology, 2019)
Biochar application to croplands has been proposed as a potential strategy to decrease losses of soil‐reactive nitrogen (N) to the air and water. However, the extent and spatial variability of biochar function at the global level are still unclear. Using Random Forest regression modelling of machine learning based on data compiled from the literature, we mapped the impacts of different biochar types (derived from wood, straw, or manure), and their interactions with biochar application rates, soil properties, and environmental factors, on soil N losses ( NH 3 volatilization, N 2 O emissions, and N leaching) and crop productivity. The results show that a suitable distribution of biochar across global croplands (i.e., one application of −1 wood biochar for poorly buffered soils, such as those characterized by soil pH 30%; and one application of −1 wood biochar, −1 straw biochar, or −1 manure biochar for other soils) could achieve an increase in global crop yields by 222–766 Tg yr −1 (4%–16% increase), a mitigation of cropland N 2 O emissions by 0.19–0.88 Tg N yr −1 (6%–30% decrease), a decline of cropland N leaching by 3.9–9.2 Tg N yr −1 (12%–29% decrease), but also a fluctuation of cropland NH 3 volatilization by −1.9–4.7 Tg N yr −1 (−12%–31% change). The decreased sum of the three major reactive N losses amount to 1.7–9.4 Tg N yr −1 , which corresponds to 3%–14% of the global cropland total N loss. Biochar generally has a larger potential for decreasing soil N losses but with less benefits to crop production in temperate regions than in tropical regions.

The urgent need for microbiology literacy in society - Kenneth Timmis; Ricardo Cavicchioli; José Luis Garcia; Balbina Nogales; Max Chavarría; Lisa Stein; Terry J. McGenity; Nicole Webster; Brajesh K. Singh; Jo Handelsman; Victor de Lorenzo; Carla Pruzzo; et al. (Environmental Microbiology, 2019)

The role of heterogeneous environment and docetaxel gradient in the emergence of polyploid, mesenchymal and resistant prostate cancer cells - Ke-Chih Lin; Gonzalo Torga; Yusha Sun; Robert Axelrod; Kenneth J. Pienta; James C. Sturm; Robert H. Austin (Clinical & Experimental Metastasis, 2019)

Understanding the evolving phenotype of vascular complications in telomere biology disorders - Cecilia Higgs; Yanick J. Crow; Denise M. Adams; Emmanuel Chang; Don Hayes; Utz Herbig; James N. Huang; Ryan Himes; Kunal Jajoo; F. Brad Johnson; Susan D. Reynolds; Yoshihiro Yonekawa; et al. (Angiogenesis, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Two key features influencing community assembly processes at regional scale: Initial state and degree of change in environmental conditions - Youzhi Feng; Ruirui Chen; James C. Stegen; Zhiying Guo; Jianwei Zhang; Zhongpei Li; Xiangui Lin (Molecular Ecology, 2018)
Belowground microbial communities strongly influence ecosystem function such that predicting function may rely on understanding ecological processes that assemble communities. Uncertainty remains, however, in what governs the relative contributions of different ecological processes. To help fill this knowledge gap, we test the general hypothesis that both initial state and degree of change in environmental conditions govern the relative contributions of different ecological assembly processes. To do so, we leveraged regional‐scale nutrient and organic matter addition experiments and used soil organic matter (SOM) as a proxy of integrated soil environmental conditions. Consistent with our hypothesis, we found that both the initial amount of SOM and the degree of change in SOM—in response to nutrient addition—influenced the relative contributions of different ecological assembly processes. These influences were most clearly observed at the regional scale, suggesting potential scale dependence. More specifically, nutrient additions homogenized bacterial community composition due to enhanced influences of homogenizing dispersal when SOM content was initially high. In contrast, nutrient additions led to divergence in community composition due to variable selection when initial SOM was low and/or when SOM increased significantly in response to nutrient additions. Our findings indicate important connections among initial conditions, degree of change in environmental variables and microbial community assembly processes that may influence ecosystem processes. These conceptual inferences highlight a need to strengthen connections between ecological theory and biogeochemical modelling.

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Reach and messages of the world's largest ivory burn - Alexander Braczkowski; Matthew H. Holden; Christopher O'Bryan; Chi‐Yeung Choi; Xiaojing Gan; Nicholas Beesley; Yufang Gao; James Allan; Peter Tyrrell; Daniel Stiles; Peadar Brehony; Revocatus Meney; et al. (Conservation Biology, 2018)
Recent increases in ivory poaching have depressed African elephant populations. Successful enforcement has led to ivory stockpiling. Stockpile destruction is becoming increasingly popular, and most destruction has occurred in the last 5 years. Ivory destruction is intended to send a strong message against ivory consumption, both in promoting a taboo on ivory use and catalyzing policy change. However, there has been no effort to establish the distribution and extent of media reporting on ivory destruction events globally. We analyzed media coverage of the largest ivory destruction event in history (Kenya, 30 April 2016) across 11 nation states connected to ivory trade. We used an online‐media crawling tool to search online media outlets and subjected 5 of the largest print newspapers (by circulation) in 5 nations of interest to content analysis. Most online news on the ivory burn came from the United States (81% of 1944 articles), whereas most of the print news articles came from Kenya (61% of 157 articles). Eighty‐six to 97% of all online articles reported the burn as a positive conservation action, whereas 4–50% discussed ivory burning as having a negative impact on elephant conservation. Most articles discussed law enforcement and trade bans as effective for elephant conservation. There was more relative search interest globally in the 2016 Kenyan ivory burn than any other burn in 5 years. Ours is the first attempt to track the reach of media coverage relative to an ivory burn and provides a case study in tracking the effects of a conservation‐marketing event.

The coexistence of copy number variations (CNVs) and single nucleotide polymorphisms (SNPs) at a locus can result in distorted calculations of the significance in associating SNPs to disease - Jiaqi Liu; Yangzhong Zhou; Sen Liu; Xiaofei Song; Xin-Zhuang Yang; Yanhui Fan; Weisheng Chen; Zeynep Coban Akdemir; Zihui Yan; Yuzhi Zuo; Renqian Du; Zhenlei Liu; et al. (Human Genetics, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Impacts of Ocean Warming on Acoustic Propagation Over Continental Shelf and Slope Regions - James Lynch; Glen Gawarkiewicz; Ying-Tsong Lin; Timothy Duda; Arthur Newhall (Oceanography, 2018)

How does biochar influence soil N cycle? A meta-analysis - Qi Liu; Yanhui Zhang; Benjuan Liu; James E. Amonette; Zhibin Lin; Gang Liu; Per Ambus; Zubin Xie (Plant and Soil, 2018)

The Benefits of Reduced Anthropogenic Climate changE (BRACE): a synthesis - Brian C. O’Neill; James M. Done; Andrew Gettelman; Peter Lawrence; Flavio Lehner; Jean-Francois Lamarque; Lei Lin; Andrew J. Monaghan; Keith Oleson; Xiaolin Ren; Benjamin M. Sanderson; Claudia Tebaldi; et al. (Climatic Change, 2018)

Acclimation of bloom‐forming and perennial seaweeds to elevated p CO 2 conserved across levels of environmental complexity - Dong Xu; Charlotte‐Elisa Schaum; Fan Lin; Ke Sun; James R. Munroe; Xiao W. Zhang; Xiao Fan; Lin H. Teng; Yi T. Wang; Zhi M. Zhuang; Naihao Ye (Global Change Biology, 2017)
Macroalgae contribute approximately 15% of the primary productivity in coastal marine ecosystems, fix up to 27.4 Tg of carbon per year, and provide important structural components for life in coastal waters. Despite this ecological and commercial importance, direct measurements and comparisons of the short‐term responses to elevated p CO 2 in seaweeds with different life‐history strategies are scarce. Here, we cultured several seaweed species (bloom forming/nonbloom forming/perennial/annual) in the laboratory, in tanks in an indoor mesocosm facility, and in coastal mesocosms under p CO 2 levels ranging from 400 to 2,000 μatm. We find that, across all scales of the experimental setup, ephemeral species of the genus Ulva increase their photosynthesis and growth rates in response to elevated p CO 2 the most, whereas longer‐lived perennial species show a smaller increase or a decrease. These differences in short‐term growth and photosynthesis rates are likely to give bloom‐forming green seaweeds a competitive advantage in mixed communities, and our results thus suggest that coastal seaweed assemblages in eutrophic waters may undergo an initial shift toward communities dominated by bloom‐forming, short‐lived seaweeds.

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Nitrogen footprints: Regional realities and options to reduce nitrogen loss to the environment - Hideaki Shibata; James N. Galloway; Allison M. Leach; Lia R. Cattaneo; Laura Cattell Noll; Jan Willem Erisman; Baojing Gu; Xia Liang; Kentaro Hayashi; Lin Ma; Tommy Dalgaard; Morten Graversgaard; et al. (Ambio, 2017)

Regulation of mitochondrial metabolism during hibernation by reversible suppression of electron transport system enzymes - Katherine E. Mathers; Sarah V. McFarlane; Lin Zhao; James F. Staples (Journal of Comparative Physiology B, 2017)

Potassium channels in the Cx43 gap junction perinexus modulate ephaptic coupling: an experimental and modeling study - Rengasayee Veeraraghavan; Joyce Lin; James P. Keener; Robert Gourdie; Steven Poelzing (Pflügers Archiv - European Journal of Physiology, 2016)

Urban high-resolution fossil fuel CO2 emissions quantification and exploration of emission drivers for potential policy applications - Risa Patarasuk; Kevin Robert Gurney; Darragh O’Keeffe; Yang Song; Jianhua Huang; Preeti Rao; Martin Buchert; John C. Lin; Daniel Mendoza; James R. Ehleringer (Urban Ecosystems, 2016)

Biogeographic patterns of soil diazotrophic communities across six forests in the North America - Qichao Tu; Ye Deng; Qingyun Yan; Lina Shen; Lu Lin; Zhili He; Liyou Wu; Joy D. Van Nostrand; Vanessa Buzzard; Sean T. Michaletz; Brian J. Enquist; Michael D. Weiser; et al. (Molecular Ecology, 2016)
Soil diazotrophs play important roles in ecosystem functioning by converting atmospheric N 2 into biologically available ammonium. However, the diversity and distribution of soil diazotrophic communities in different forests and whether they follow biogeographic patterns similar to macroorganisms still remain unclear. By sequencing nifH gene amplicons, we surveyed the diversity, structure and biogeographic patterns of soil diazotrophic communities across six North American forests (126 nested samples). Our results showed that each forest harboured markedly different soil diazotrophic communities and that these communities followed traditional biogeographic patterns similar to plant and animal communities, including the taxa–area relationship ( TAR ) and latitudinal diversity gradient. Significantly higher community diversity and lower microbial spatial turnover rates (i.e. z ‐values) were found for rainforests (~0.06) than temperate forests (~0.1). The gradient pattern of TAR s and community diversity was strongly correlated ( r 2 > 0.5) with latitude, annual mean temperature, plant species richness and precipitation, and weakly correlated ( r 2 pH and soil moisture. This study suggests that even microbial subcommunities (e.g. soil diazotrophs) follow general biogeographic patterns (e.g. TAR , latitudinal diversity gradient), and indicates that the metabolic theory of ecology and habitat heterogeneity may be the major underlying ecological mechanisms shaping the biogeographic patterns of soil diazotrophic communities.

Aesthetic preference recognition of 3D shapes using EEG - Lin Hou Chew; Jason Teo; James Mountstephens (Cognitive Neurodynamics, 2016)

Resolving the ancestry of Austronesian-speaking populations - Pedro A. Soares; Jean A. Trejaut; Teresa Rito; Bruno Cavadas; Catherine Hill; Ken Khong Eng; Maru Mormina; Andreia Brandão; Ross M. Fraser; Tse-Yi Wang; Jun-Hun Loo; Christopher Snell; et al. (Human Genetics, 2016)

Static and dynamic posterior cingulate cortex nodal topology of default mode network predicts attention task performance - Pan Lin; Yong Yang; Jorge Jovicich; Nicola De Pisapia; Xiang Wang; Chun S. Zuo; James Jonathan Levitt (Brain Imaging and Behavior, 2016)

Prior human polyomavirus and papillomavirus infection and incident lung cancer: a nested case–control study - Danny V. Colombara; Lisa E. Manhart; Joseph J. Carter; Stephen E. Hawes; Noel S. Weiss; James P. Hughes; Matt J. Barnett; Gary E. Goodman; Jennifer S. Smith; You-Lin Qiao; Denise A. Galloway (Cancer Causes & Control, 2015)

Extracellular sodium and potassium levels modulate cardiac conduction in mice heterozygous null for the Connexin43 gene - Sharon A. George; Katherine J. Sciuto; Joyce Lin; Mohamed E. Salama; James P. Keener; Robert G. Gourdie; Steven Poelzing (Pflügers Archiv - European Journal of Physiology, 2015)

Sodium channels in the Cx43 gap junction perinexus may constitute a cardiac ephapse: an experimental and modeling study - Rengasayee Veeraraghavan; Joyce Lin; Gregory S. Hoeker; James P. Keener; Robert G. Gourdie; Steven Poelzing (Pflügers Archiv - European Journal of Physiology, 2015)

Graph-Cut-Based Segmentation of Proximal Femur from Computed Tomography Images with Shape Prior - Junbin Huang; James F. Griffith; Defeng Wang; Lin Shi (Journal of Medical and Biological Engineering, 2015)

Erratum to: Reliability of Postmortem Fentanyl Concentrations in Determining the Cause of Death - James R. Gill; Peter T. Lin; Lewis Nelson (Journal of Medical Toxicology, 2015)

Advanced neuroimaging applied to veterans and service personnel with traumatic brain injury: state of the art and potential benefits - Elisabeth A. Wilde; Sylvain Bouix; David F. Tate; Alexander P. Lin; Mary R. Newsome; Brian A. Taylor; James R. Stone; James Montier; Samuel E. Gandy; Brian Biekman; Martha E. Shenton; Gerald York (Brain Imaging and Behavior, 2015)

Effects of the subtropical anticyclones over North Africa and Arabian Peninsula on the African easterly jet - James Spinks; Yuh‐Lang Lin; Ademe Mekonnen (International Journal of Climatology, 2015)
North African climate is analysed between 1979 and 2010 with an emphasis on August using the European Center for Medium‐Range Weather Forecast ( ECMWF ) global dataset to investigate the effects of the subtropical anticyclones over North Africa and the Arabian Peninsula on the African easterly jet ( AEJ ). It was found that the AEJ encloses a core with a local wind maximum ( LWM ) in both West and East Africa, in which the west LWM core has a higher zonal wind speed. The strength of both cores is distinctly different by way of thermal wind balance. As found in previous studies, the AEJ is formed through baroclinicity with influence from Saharan lower level heating along and to the north of the Intertropical Front ( ITF ). As there are two separate anticyclonic centres, the AEJ is maintained by the anticyclonic systems in West Africa, East Africa as well as the Arabian Peninsula. The presence of these two anticyclonic centres provides the AEJ with two separate core maxima with the western LWM located at 15°W, 17°N and the eastern LWM located at 35°E, 15°N for August.

Association of novelty-related behaviors and intravenous cocaine self-administration in Diversity Outbred mice - Price E. Dickson; Juliet Ndukum; Troy Wilcox; James Clark; Brittany Roy; Lifeng Zhang; Yun Li; Da-Ting Lin; Elissa J. Chesler (Psychopharmacology, 2015)

Amphipol-Trapped ExbB–ExbD Membrane Protein Complex from Escherichia coli: A Biochemical and Structural Case Study - Aleksandr Sverzhinsky; Shuo Qian; Lin Yang; Marc Allaire; Isabel Moraes; Dewang Ma; Jacqueline W. Chung; Manuela Zoonens; Jean-Luc Popot; James W. Coulton (The Journal of Membrane Biology, 2014)

Lung Cancer Stem Cells and Implications for Future Therapeutics - Jing Wang; Ze-hong Li; James White; Lin-bo Zhang (Cell Biochemistry and Biophysics, 2014)

Sympatric Asian felid phylogeography reveals a major Indochinese–Sundaic divergence - Shu‐Jin Luo; Yue Zhang; Warren E. Johnson; Lin Miao; Paolo Martelli; Agostinho Antunes; James L. D. Smith; Stephen J. O'Brien (Molecular Ecology, 2014)
The dynamic geological and climatological history of Southeast Asia has spawned a complex array of ecosystems and 12 of the 37 known cat species, making it the most felid‐rich region in the world. To examine the evolutionary histories of these poorly studied fauna, we compared phylogeography of six species (leopard cat Prionailurus bengalensis , fishing cat P. viverrinus , Asiatic golden cat Pardofelis temminckii , marbled cat P. marmorata , tiger Panthera tigris and leopard P. pardus ) by sequencing over 5 kb of DNA each from 445 specimens at multiple loci of mt DNA , Y and X chromosomes. All species except the leopard displayed significant phylogenetic partitions between Indochina and Sundaland, with the central Thai–Malay Peninsula serving as the biogeographic boundary. Concordant mt DNA and nuclear DNA genealogies revealed deep Indochinese–Sundaic divergences around 2 MYA in both P. bengalensis and P. marmorata comparable to previously described interspecific distances within Felidae. The divergence coincided with serial sea level rises during the late Pliocene and early Pleistocene, and was probably reinforced by repeated isolation events associated with environmental changes throughout the Pleistocene. Indochinese–Sundaic differentiations within P. tigris and P. temminckii were more recent at 72–108 and 250–1570 kya, respectively. Overall, these results illuminate unexpected, deep vicariance events in Southeast Asian felids and provide compelling evidence of species‐level distinction between the Indochinese and Sundaic populations in the leopard cat and marbled cat. Broader sampling and further molecular and morphometric analyses of these species will be instrumental in defining conservation units and effectively preserving Southeast Asian biodiversity.

Ferulic acid increases pain threshold and ameliorates depression-like behaviors in reserpine-treated mice: behavioral and neurobiological analyses - Ying Xu; Lu Zhang; Tuo Shao; Lina Ruan; Lin Wang; Jiao Sun; Jianxin Li; Xinbo Zhu; James M. O’Donnell; Jianchun Pan (Metabolic Brain Disease, 2013)

Augmenting satellite precipitation estimation with lightning information - Majid Mahrooghy; Valentine G. Anantharaj; Nicolas H. Younan; Walter A. Petersen; Kuo-Lin Hsu; Ali Behrangi; James Aanstoos (International Journal of Remote Sensing, 2013)

Warming up to climate change: a participatory approach to engaging with agricultural stakeholders in the Southeast US - Wendy-Lin Bartels; Carrie A. Furman; David C. Diehl; Fred S. Royce; Daniel R. Dourte; Brenda V. Ortiz; David F. Zierden; Tracy A. Irani; Clyde W. Fraisse; James W. Jones (Regional Environmental Change, 2013)

Origin of the pre-tropical storm Debby (2006) African easterly wave-mesoscale convective system - Yuh-Lang Lin; Liping Liu; Guoqing Tang; James Spinks; Wilson Jones (Meteorology and Atmospheric Physics, 2013)

Toxicity of Trimethyltin and Dimethyltin in Rats and Mice - Xiaojiang Tang; Xin Wu; Amber M. Dubois; Gang Sui; Banghua Wu; Guanchao Lai; Zhihong Gong; Hongbin Gao; Shenglai Liu; Zhiyong Zhong; Zhongning Lin; James Olson; et al. (Bulletin of Environmental Contamination and Toxicology, 2013)

Reliability of Postmortem Fentanyl Concentrations in Determining the Cause of Death - James R. Gill; Peter T. Lin; Lewis Nelson (Journal of Medical Toxicology, 2013)

Reframing social sustainability reporting: towards an engaged approach - Liam Magee; Andy Scerri; Paul James; James A. Thom; Lin Padgham; Sarah Hickmott; Hepu Deng; Felicity Cahill (Environment, Development and Sustainability, 2013)

Activity of the Arabidopsis RD29A and RD29B promoter elements in soybean under water stress - Saadia Bihmidine; Jiusheng Lin; Julie M. Stone; Tala Awada; James E. Specht; Tom E. Clemente (Planta, 2013)

The Bxb1 Recombinase Mediates Site-Specific Deletion in Transgenic Wheat - Ann Blechl; Jeanie Lin; Min Shao; Roger Thilmony; James Thomson (Plant Molecular Biology Reporter, 2012)

Reproductive hormones and interleukin-6 in serious leisure male athletes - Leah Z. FitzGerald; Wendie A. Robbins; James S. Kesner; Lin Xun (European Journal of Applied Physiology, 2012)

Bacterially mediated iron cycling and associated biogeochemical processes in a subtropical shallow coastal aquifer: implications for groundwater quality - Chaofeng Lin; Eloise I. Larsen; Genevieve R. Larsen; Malcolm E. Cox; James J. Smith (Hydrobiologia, 2012)

Microcosm Study of Iron Mobilization and Greenhouse Gas Evolution in Soils of a Plantation-Forested Subtropical Coastal Catchment - Chaofeng Lin; Eloise I. Larsen; Peter R. Grace; James J. Smith (Water, Air, & Soil Pollution, 2012)

Climate Change Effects on Hydrology and Ecology of Wetlands in the Mid-Atlantic Highlands - Jonathan L. Pitchford; Chenjie Wu; LianShin Lin; J. Todd Petty; Richard Thomas; Walter E. Veselka; Danny Welsch; Nicolas Zegre; James T. Anderson (Wetlands, 2012)

Liposomes Containing (-)-Gossypol-Enriched Cottonseed Oil Suppress Bcl-2 and Bcl-xL Expression in Breast Cancer Cells - Hong Li; Longzhu Piao; Pingping Xu; Weiping Ye; Saiyi Zhong; Shu-Hong Lin; Samuel K. Kulp; Yicheng Mao; Youngah Cho; L. James Lee; Robert J. Lee; Young C. Lin (Pharmaceutical Research, 2011)

Attribute-Based Design Space: Materials-Science-Based Quality-By-Design for Operational Flexibility and Process Portability - James N. Michaels; Holly Bonsignore; Buffy L. Hudson-Curtis; Steven Laurenz; Hung-Ren Homer Lin; Thomas Mathai; Girish Pande; Ashlesh Sheth; Omar Sprockel (Journal of Pharmaceutical Innovation, 2011)

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

Factors affecting lipid accumulation by Nannochloropsis oculata in a two-stage cultivation process - Chia-Hung Su; Liang-Jung Chien; James Gomes; Yu-Sheng Lin; Yuan-Kun Yu; Jhang-Song Liou; Rong-Jhih Syu (Journal of Applied Phycology, 2011)

Decreased expression of Flightless I, a gelsolin family member and developmental regulator, in early-gestation fetal wounds improves healing - Cheng-Hung Lin; James M. Waters; Barry C. Powell; Ruth M. Arkell; Allison J. Cowin (Mammalian Genome, 2011)

Involvement of Arbuscular Mycorrhizal Symbiosis in the Distribution of Sawgrass and Cattail in Florida Everglades - Li Lin; James Webb; Xing-Hai Zhang (Wetlands, 2011)

Influence of indomethacin on the ventilatory and cerebrovascular responsiveness to hypoxia - Jui-Lin Fan; Keith R. Burgess; Kate N. Thomas; Karen C. Peebles; Samuel J. E. Lucas; Rebekah A. I. Lucas; James D. Cotter; Philip N. Ainslie (European Journal of Applied Physiology, 2011)

A nationally consistent framework for identifying interstate waters with applications for the national listing of fish advisories - William Cooter; Patricia Cunningham; James Rineer; Brandon Bergenroth; Shu-yi Lin (Environmental Monitoring and Assessment, 2011)

BNIP3 induces IL6 and calcineurin/NFAT3 hypertrophic-related pathways in H9c2 cardiomyoblast cells - Yi-Jiun Weng; Wei-Wen Kuo; Chia-Hua Kuo; Kwong-Chung Tung; Chang-Hai Tsai; James A. Lin; Fuu-Jen Tsai; Dennis Jine-Yuan Hsieh; Chih-Yang Huang; Jin-Ming Hwang (Molecular and Cellular Biochemistry, 2010)

17β-Estradiol inhibits prostaglandin E2-induced COX-2 expressions and cell migration by suppressing Akt and ERK1/2 signaling pathways in human LoVo colon cancer cells - Tung-Yuan Lai; Li-Mien Chen; Jing-Ying Lin; Bor-Show Tzang; James A. Lin; Chang-Hai Tsai; Yueh-Min Lin; Chih-Yang Huang; Chung-Jung Liu; Hsi-Hsien Hsu (Molecular and Cellular Biochemistry, 2010)

E4BP4 is a cardiac survival factor and essential for embryonic heart development - Yi-Jiun Weng; Dennis Jine-Yuan Hsieh; Wei-Wen Kuo; Tung-Yuan Lai; Hsi-Hsien Hsu; Chang-Hai Tsai; Fuu-Jen Tsai; Ding-Yu Lin; James A. Lin; Chih-Yang Huang; Kwong-Chung Tung (Molecular and Cellular Biochemistry, 2010)

Dopaminergic neurotoxicity following pulmonary exposure to manganese-containing welding fumes - Krishnan Sriram; Gary X. Lin; Amy M. Jefferson; Jenny R. Roberts; Rebecca S. Chapman; Bean T. Chen; Joleen M. Soukup; Andrew J. Ghio; James M. Antonini (Archives of Toxicology, 2010)

Dual bio-responsive gene delivery via reducible poly(amido amine) and survivin-inducible plasmid DNA - Ran Namgung; Jonathan H. Brumbach; Ji Hoon Jeong; James W. Yockman; Sung Wan Kim; Chao Lin; Zhiyuan Zhong; Jan Feijen; Johan F. J. Engbersen; Won Jong Kim (Biotechnology Letters, 2010)

Skin cooling aids cerebrovascular function more effectively under severe than moderate heat stress - Rebekah A. I. Lucas; Philip N. Ainslie; Jui-Lin Fan; Luke C. Wilson; Kate N. Thomas; James D. Cotter (European Journal of Applied Physiology, 2010)

Response of benthic macroinvertebrate communities to highway construction in an Appalachian watershed - Lara B. Hedrick; Stuart A. Welsh; James T. Anderson; Lian-Shin Lin; Yushun Chen; Xinchao Wei (Hydrobiologia, 2010)

Transcriptome analysis during somatic embryogenesis of the tropical monocot Elaeis guineensis: evidence for conserved gene functions in early development - Hsiang-Chun Lin; Fabienne Morcillo; Stéphane Dussert; Christine Tranchant-Dubreuil; James W. Tregear; Timothy John Tranbarger (Plant Molecular Biology, 2009)

Hypoxia-induced compensatory effect as related to Shh and HIF-1α in ischemia embryo rat heart - Jin-Ming Hwang; Yi-Jiun Weng; James A. Lin; Da-Tian Bau; Fu-Yang Ko; Fuu-Jen Tsai; Chang-Hai Tsai; Chieh-Hsi Wu; Pei-Cheng Lin; Chih-Yang Huang; Wei-Wen Kuo (Molecular and Cellular Biochemistry, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

A brief summary of Dr. G. V. Rao’s research interests - Yeong-Jer Lin; James T. Moore; Jack Fishman (Natural Hazards, 2007)

Evaluation of an Alkyne-containing Analogue of Farnesyl Diphosphate as a Dual Substrate for Protein-prenyltransferases - Ayako Hosokawa; James W. Wollack; Zhiyuan Zhang; Lin Chen; George Barany; Mark D. Distefano (International Journal of Peptide Research and Therapeutics, 2007)

Conservation of Heathland Ground Beetles (Coleoptera, Carabidae): The Value of Lowland Coniferous Plantations - Ying-Chi Lin; Robert James; Paul M. Dolman (Biodiversity and Conservation, 2007)

Overexpression of proline oxidase induces proline-dependent and mitochondria-mediated apoptosis - Chien-an A. Hu; Steven P. Donald; Jian Yu; Wei-Wen Lin; Zhihe Liu; Gary Steel; Cassandra Obie; David Valle; James M. Phang (Molecular and Cellular Biochemistry, 2007)

Apoptotic and anti-proliferative effects of 17β-estradiol and 17β-estradiol-like compounds in the Hep3B cell line - Erh-Jung Huang; Cheng-Chung Wu; Hsien-Ping Huang; Jer-Yuh Liu; Chung-Sheng Lin; Yan-Zin Chang; James A. Lin; Jaung-Geng Lin; Li-Mien Chen; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Phenotypic characterization of Bbs4 null mice reveals age-dependent penetrance and variable expressivity - Erica R. Eichers; Muhammad M. Abd-El-Barr; Richard Paylor; Richard Alan Lewis; Weimin Bi; Xiaodi Lin; Thomas P. Meehan; David W. Stockton; Samuel M. Wu; Elizabeth Lindsay; Monica J. Justice; Philip L. Beales; et al. (Human Genetics, 2006)

Opposing Action of Estrogen Receptors α and β on Tumor Necrosis Factor-α Gene Expression and Caspase-8-mediated Apoptotic Effects in HA22T Cells - Erh-Jung Huang; Cheng-Chung Wu; Shin-Da Lee; Juen-Hau Chen; Jer-Yuh Liu; Jiunn-Liang Ko; James A. Lin; Min-Chi Lu; Li-Mien Chen; Chih-Yang Huang; Wei-Wen Kuo (Molecular and Cellular Biochemistry, 2006)

Cardiomyoblast apoptosis induced by insulin-like growth factor (IGF)-I resistance is IGF-II dependent and synergistically enhanced by angiotensin II - Wei-Wen Kuo; Chung-Jung Liu; Li-Ming Chen; Chieh-Hsi Wu; Chun-Hsien Chu; Jer-Yuh Liu; Min-Chi Lu; James A. Lin; Shin-Da Lee; Chih-Yang Huang (Apoptosis, 2006)

Climatic Change, Wars and Dynastic Cycles in China Over the Last Millennium - David D. Zhang; C. Y. Jim; George C-S Lin; Yuan-Qing He; James J. Wang; Harry F. Lee (Climatic Change, 2006)

Upregulation of iron regulatory proteins and divalent metal transporter-1 isoforms in the rat hippocampus after kainate induced neuronal injury - En Huang; Wei-Yi Ong; Mei-Lin Go; James R. Connor (Experimental Brain Research, 2006)

Coffee and tomato share common gene repertoires as revealed by deep sequencing of seed and cherry transcripts - Chenwei Lin; Lukas A. Mueller; James Mc Carthy; Dominique Crouzillat; Vincent Pétiard; Steven D. Tanksley (Theoretical and Applied Genetics, 2005)

Spectral and Kinetic Analysis of the Energy Coupling in the PS I–LHC I Supercomplex from the Green Alga Chlamydomonas reinhardtii at 77 K - Alexander N. Melkozernov; Joanna Kargul; Su Lin; James Barber; Robert E. Blankenship (Photosynthesis Research, 2005)

Identification of a Single Nucleotide Polymorphism in Porcine Testis Cytochrome P450-c17 (CYP17) and Its Effect on Steroidogenesis - Zhihong Lin; Yanping Lou; E. James Squires (Biochemical Genetics, 2005)

Mapping QTLs of traits contributing to yield and analysis of genetic effects in tetraploid cotton - Dao-Hua He; Zhong-Xu Lin; Xian-Long Zhang; Yi-Chun Nie; Xiao-Ping Guo; Chun-Da Feng; James McD. Stewart (Euphytica, 2005)

A novel polymorphism in the 5′ untranslated region of theporcine cytochrome b5 (CYB5) gene is associated with decreased fat androstenone level - Zhihong Lin; Yanping Lou; John Peacock; E. James Squires (Mammalian Genome, 2005)

Cocaine increases human immunodeficiency virus type 1 neuroinvasion through remodeling brain microvascular endothelial cells - Milan Fiala; Amy J Eshleman; John Cashman; Justin Lin; Albert S Lossinsky; Vannina Suarez; Wendy Yang; Jun Zhang; Waldemar Popik; Elyse Singer; Francesco Chiappelli; Eva Carro; et al. (Journal of NeuroVirology, 2005)

Molecular cloning and functional analysis of porcine SULT1A1 gene and its variant: a single mutation SULT1A1 causes a significant decrease in sulfation activity - Zhihong Lin; Yanping Lou; James E. Squires (Mammalian Genome, 2004)

Software GPS Receiver - Vasu Chakravarthy; James Tsui; David Lin; John Schamus (GPS Solutions, 2001)

Comparative physical mapping of targeted regions of the rat genome - Tyrone J. Summers; James W. Thomas; Shih-Queen Lee-Lin; Valerie V.B. Maduro; Jacquelyn R. Idol; Eric D. Green (Mammalian Genome, 2001)

Time-dependent responses of soil CO2 efflux components to elevated atmospheric [CO2] and temperature in experimental forest mesocosms - Guanghui Lin; Paul T. Rygiewicz; James R. Ehleringer; Mark G. Johnson; David T. Tingey (Plant and Soil, 2001)

Human-mouse comparative mapping of the genomic region containing CDK6: localization of an evolutionary breakpoint - James W. Thomas; Shih-Queen Lee-Lin; Eric D. Green (Mammalian Genome, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Elevated CO 2 and temperature impacts on different components of soil CO 2 efflux in Douglas‐fir terracosms - Guanghui Lin; James R. Ehleringer; PauL. T. Rygiewicz; Mark G. Johnson; David T. Tingey (Global Change Biology, 1999)
Although numerous studies indicate that increasing atmospheric CO 2 or temperature stimulate soil CO 2 efflux, few data are available on the responses of three major components of soil respiration [i.e. rhizosphere respiration (root and root exudates), litter decomposition, and oxidation of soil organic matter] to different CO 2 and temperature conditions. In this study, we applied a dual stable isotope approach to investigate the impact of elevated CO 2 and elevated temperature on these components of soil CO 2 efflux in Douglas‐fir terracosms. We measured both soil CO 2 efflux rates and the 13 C and 18 O isotopic compositions of soil CO 2 efflux in 12 sun‐lit and environmentally controlled terracosms with 4‐year‐old Douglas fir seedlings and reconstructed forest soils under two CO 2 concentrations (ambient and 200 ppmv above ambient) and two air temperature regimes (ambient and 4 °C above ambient). The stable isotope data were used to estimate the relative contributions of different components to the overall soil CO 2 efflux. In most cases, litter decomposition was the dominant component of soil CO 2 efflux in this system, followed by rhizosphere respiration and soil organic matter oxidation. Both elevated atmospheric CO 2 concentration and elevated temperature stimulated rhizosphere respiration and litter decomposition. The oxidation of soil organic matter was stimulated only by increasing temperature. Release of newly fixed carbon as root respiration was the most responsive to elevated CO 2 , while soil organic matter decomposition was most responsive to increasing temperature. Although some assumptions associated with this new method need to be further validated, application of this dual‐isotope approach can provide new insights into the responses of soil carbon dynamics in forest ecosystems to future climate changes.

Biomimetic Metabolism of Artelinic Acid by Chemical Cytochrome P-450 Model Systems - Olutosin R. Idowu; Ai J. Lin; James M. Grace; James O. Peggins (Pharmaceutical Research, 1997)

The pharmacokinetics and pharmacodynamics of adinazolam: multi-ethnic comparisons - Kotra Ajir; Michael Smith; Keh-Ming Lin; Dora Anderson; Inocencia Nuccio; Yanping Zheng; Russell E. Poland; Joseph C. Fleishaker; James H. Chambers (Psychopharmacology, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)